2017
DOI: 10.1016/j.jdent.2017.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Delayed photo-activation and addition of thio-urethane: Impact on polymerization kinetics and stress of dual-cured resin cements

Abstract: Objective 1) to determine the moment during the redox polymerization reaction of dual cure cements at which to photo-activate the material in order to reduce the polymerization stress, and 2) to evaluate possible synergistic effects between adding chain transfer agents and delayed photo-activation. Methods The two pastes of an experimental dual-cure material were mixed, and the polymerization kinetics of the redox phase was followed. The moment when the material reached its maximum rate of redox polymerizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 36 publications
1
16
1
1
Order By: Relevance
“…Furthermore, thiol-methacrylate reactions delay the gelation and vitrification stages of polymerization via chain-transfer reactions, with consequent higher conversion and lower stress [1723]. However, in the present study, silanization with thiols or thiourethanes did not affect RP max , DC at RP max nor ultimate DC.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Furthermore, thiol-methacrylate reactions delay the gelation and vitrification stages of polymerization via chain-transfer reactions, with consequent higher conversion and lower stress [1723]. However, in the present study, silanization with thiols or thiourethanes did not affect RP max , DC at RP max nor ultimate DC.…”
Section: Discussioncontrasting
confidence: 55%
“…The rationale is that the thiol functional groups work as chain transfer agents to promote a radically assisted step-growth polymerization of methacrylates [18,19]. In fact, several prior studies demonstrated the effectiveness of the addition of thiourethane oligomers on polymerization stress reduction and depth of polymerization increase, which in turn relates to the high refractive index of these oligomers [2023]. …”
Section: Introductionmentioning
confidence: 99%
“…Though not without controversy, slower rates of polymerization have been associated with lower polymerization stress . In this study, despite the increase in Rp max observed in materials in which the filler was functionalized with thiourethane, the stress values were actually lower, irrespective of the filler type evaluated (Table and Figure ).…”
Section: Resultsmentioning
confidence: 56%
“…In this study, despite the increase in Rp max observed in materials in which the filler was functionalized with thiourethane, the stress values were actually lower, irrespective of the filler type evaluated (Table and Figure ). As mentioned, this could be partially due to the delayed vitrification, in which the modulus development is delayed to later stages in conversion, thus, accommodating part of the stress via chain rearrangement . However, the only slight increases in DC at Rp max (3–5%) is not sufficient to explain stress reductions of about 10–20% between methacrylate and thiourethane fillers, within the same filler type.…”
Section: Resultsmentioning
confidence: 96%
“…Dual-cured resin cements provides the advantages of both light and chemically activated resins, reach adequate degree of polymerization and provide an extended working time due to the easily controlled light-curing mechanism. As a result, a fast initial setting of the resin cement contributes to a stabilization of the restoration (Yoshida and Atsuta, 2006, Faria-E-Silva and Pfeifer, 2017). A resin cement should be able to achieve a high degree of monomer conversion, which guarantees a more effective sealing ability, lower solubility of the cement, higher bond strength and superior color stability of the cement (Archegas et al, 2011, Lohbauer et al, 2010, Kumbuloglu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%